Dialogiczność jako warunek konstytuowania się podmiotu. Refleksje wokół Sporu o podmiotowość - Skrzypczak, Alicja (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2016)
The aim of the paper is to show the conditions of subjectivity constitution in terms of dialogue and the figure of the Other. The analytical and hermeneutical approach I hold is the foundation of interdisciplinary attempt to describe possible concepts of shared relation of the terms: consciousness, subjectivity and identity. The three appear to be recognized only in the ethical situation. It requires taking responsibility for the Other, for giving him the identity which mirrors one’s subjectivity. In this way the subject learns the limits and chances for gaining self-knowledge. The paper also presents a new approach towards redefining the definition of subjectivity, which includes artificially and medically enhanced entities.
Dialogical Preconditions of the (Self)Constitution of the Subject. Rethinking Dispute Over Subjectivity
Keywords: subjectivity; consciousness; identity; dialogue; self-knowledge; self-constitution